Spatial variability of pH and Fe2O3 content in soils of the basin Tabure river in Lara State - Hernández, Wilmer (2018)
The pH is a chemical property of the soil that represents, in general terms, its self- reaction, while iron in the form of Fe2O3 sets up a fraction related to the evolution degree of soils. With the purpose of knowing the variability of two chemical properties of the soils of Tabure river basin in Lara state, namely  pH and Fe2O3, a systematic soil survey was made in a grid of 100mx100m and classic statistic parameters were studied and one semivariography analysis with raw data. An omnidirectional semivariogram fitting to a spheric model with a range of 580m was obtained for pH and for Fe2O3 the best fit for an omnidirectional semivariogram was an exponential model with a range of 283m. In the case of pH a light anisotropy in direction nw-se was observed, while Fe2O3showed isotropic behavior. In conclusion the maximum variation distance of studied properties of soil was determined and a minor anisotropy of pH was recognized. These results are useful for future investigations about pH and Fe2O3spatial variability of soil in the studied basin.